Systematic review on the management of ileoanal pouch–vaginal fistulas after restorative proctocolectomy in the treatment of ulcerative colitis. (12th September 2020) - Machin, M.; Younan, H.‐C.; Slesser, A. A. P.; Mohsen, Y.
Abstract: Aim: Ileoanal pouch–vaginal fistula (PVF) is a relatively common complication of restorative proctocolectomy with ileal pouch–anal anastomosis. There are several operative approaches in the management of PVF. There is currently no consensus as to which approach is the most effective or which should be attempted first. Method: A systematic review was undertaken following a publicly available protocol registered with PROSPERO (CRD42019133750) in accordance with PRISMA guidelines. Online searches of databases MEDLINE and Embase, Cochrane Library, ClinicalTrials.gov, EU Clinical Trials and ISRCTN registry were performed. Results: Twenty‐seven articles met the criteria for inclusion in the study: 13 retrospective cohort studies, two prospective cohort studies, eight case series, three case reports and a case–control study. A narrative synthesis was performed due to heterogeneity between included articles. Our study included 577 PVFs, and the incidence rate was 2.1%–17.1%. Both local and abdominal approaches were used in the management of PVF. The overall success of local and abdominal procedures was 44.9% and 60.2% respectively. ROBINS‐I assessment revealed a critical risk of bias. GRADE assessment indicated a very low certainty in effect size and evidence quality. Conclusion: Local interventions and abdominal approaches have a high failure rate. The results of this review will aid the counselling of patients with this condition. Furthermore, we provide an algorithm for discussion on the management of PVF based on experience at our local centre. The studies available on the management of PVF are low quality; a large prospective registry and Delphi consensus are required to further this area of research.